2012
DOI: 10.1021/jf3021514
|View full text |Cite
|
Sign up to set email alerts
|

Germination Dramatically Increases Isoflavonoid Content and Diversity in Chickpea (Cicer arietinum L.) Seeds

Abstract: The effect of germination on bioactive components in legume seeds was investigated in terms of the antioxidant capacity and total phenolic contents. Germination increased the total phenolic content and antioxidant capacity of most seeds. Particularly in chickpea seeds, the isoflavone contents increased by over 100 fold, mainly due to the increase of formononetin and biochanin A level. As a result, these two compounds were conveniently isolated from the germinated seeds in preparative scale and structurally con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 37 publications
5
62
0
2
Order By: Relevance
“…Both, DRAC and ABTS methods, showed a similar tendency. Some researchers (Wu et al, 2012;Aguilera et al, 2013;Gharachorloo et al, 2013;Singh et al, 2014;Dueñas et al, 2016) also reported that the germination increased the AoxA of legumes. However, they did not evaluate AoxA in extracts of bound phenolics.…”
Section: Phenolic Content Flavonoid Content and Antioxidant Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…Both, DRAC and ABTS methods, showed a similar tendency. Some researchers (Wu et al, 2012;Aguilera et al, 2013;Gharachorloo et al, 2013;Singh et al, 2014;Dueñas et al, 2016) also reported that the germination increased the AoxA of legumes. However, they did not evaluate AoxA in extracts of bound phenolics.…”
Section: Phenolic Content Flavonoid Content and Antioxidant Activitymentioning
confidence: 98%
“…Wu et al (2012) reported that the germination is an effective bioprocess to increase isoflavonoids content as well as to improve the diversity of these compounds in germinated chickpea; they reported that germinated chickpea has more (4-fold) isoflavonoid content than soybean. The flavonoids have significant effects on prevention and treatment of cancer, which has been demonstrated in epidemiological studies and human clinical trials.…”
Section: Phenolic Content Flavonoid Content and Antioxidant Activitymentioning
confidence: 99%
“…Other foodstuffs in this category were black bean sauce (53-152 mg/kg fw), soy paste (57-147 mg/kg dw) and defatted soy meal (1,369 mg/kg dw), the latter being used as animal feed Thompson et al, 2006;Clarke et al, 2013a). The high level of isoflavones in miso and tofu was confirmed in studies giving the content in mg/kg dw Song et al, 1998;Wu et al, 2012). Lee et al (2002) analysed various soybean products for their total isoflavone contents.…”
Section: Isoflavones In Other Foodstuffsmentioning
confidence: 89%
“…Further, 3DWM and 5D25 were resulted to have same concentration of daidzein. According to findings of previous studies, biochanin A, formononetin, genistein, and their glycoside conjugates are the major isoflavones found in chickpeas (Wu et al, 2012). Literature have proved the presence of about 31 different isoflavones in soybean and chickpeas discovered from chromatographic techniques based on analyzing the retention time of their chromatogram, spectra obtained through UV, and their mass fragments.…”
Section: Functional Properties Analsysis Bulk Density (Bd)mentioning
confidence: 99%
“…Literature have proved the presence of about 31 different isoflavones in soybean and chickpeas discovered from chromatographic techniques based on analyzing the retention time of their chromatogram, spectra obtained through UV, and their mass fragments. According to the study of Wu et al (2012) chickpeas have almost four times more isoflavones than soybean. The isoflavones are normally identified using UV absorption spectra as it has a specific UV absorption band II with wavelength (240−280nm) to absorb A-ring benzoyl system.…”
Section: Functional Properties Analsysis Bulk Density (Bd)mentioning
confidence: 99%